1998
DOI: 10.1093/ageing/27.4.503
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal ideation and the 'wish to die' in dementia patients: the role of depression

Abstract: Objc~ctive: to determine the prevalence of self-reported suicidal ideation and the 'wish to die' in dementia patients, their association with depressive symptoms and the type of dementia. Design: the cohort was formed retrospectively of consecutive referrals between 1985 and 1994 of cognitively impaired patients who met American Psychiatric Association Diagnostic and Statistical Manual of Mental Disorders, third edition and third edition, revised, criteria for dementia. They were assessed for depression using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
62
2
3

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 28 publications
3
62
2
3
Order By: Relevance
“…Consistent with previous research, depressive symptoms and negative cognitive bias were strongly correlated in older adults (Alford et al, 1995;Andrews & Brown, 1995;Beevers & Miller, 2004;Draper et al, 1998;Forsell et al, 1997;Jorm et al, 1995;Jungwirth et al, 2004;La Rue et al, 1996;Pearman & Storandt, 2004;Scocco et al, 2001). Extensive research has found strong associations between depressive symptoms and hopelessness (Alford et al, 1995;Beevers & Miller, 2004), death thoughts (Draper et al, 1998;Forsell et al, 1997;Jorm et al, 1995;Scocco et al, 2001) and low self-esteem (Andrews & Brown, 1995;Brown et al, 1986;) both individually and as part of Beck's negative cognitive triad.…”
Section: Depression and Negative Cognitive Biassupporting
confidence: 83%
See 2 more Smart Citations
“…Consistent with previous research, depressive symptoms and negative cognitive bias were strongly correlated in older adults (Alford et al, 1995;Andrews & Brown, 1995;Beevers & Miller, 2004;Draper et al, 1998;Forsell et al, 1997;Jorm et al, 1995;Jungwirth et al, 2004;La Rue et al, 1996;Pearman & Storandt, 2004;Scocco et al, 2001). Extensive research has found strong associations between depressive symptoms and hopelessness (Alford et al, 1995;Beevers & Miller, 2004), death thoughts (Draper et al, 1998;Forsell et al, 1997;Jorm et al, 1995;Scocco et al, 2001) and low self-esteem (Andrews & Brown, 1995;Brown et al, 1986;) both individually and as part of Beck's negative cognitive triad.…”
Section: Depression and Negative Cognitive Biassupporting
confidence: 83%
“…Extensive research has found strong associations between depressive symptoms and hopelessness (Alford et al, 1995;Beevers & Miller, 2004), death thoughts (Draper et al, 1998;Forsell et al, 1997;Jorm et al, 1995;Scocco et al, 2001) and low self-esteem (Andrews & Brown, 1995;Brown et al, 1986;) both individually and as part of Beck's negative cognitive triad. Hopelessness is intimately linked to late-life depressive symptoms (Adams, Matto, & Sanders, 2004).…”
Section: Depression and Negative Cognitive Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…24,26,27 Nevertheless, suicidal behavior in demented persons might entirely be explained by the presence of depressive disorders. 6,18 It yet remains to be confirmed whether depressive disorders act as a mediator for suicide in persons with dementia. As in the general population, chronic and other somatic diseases are expected to be associated with an elevated risk of suicide among demented persons.…”
Section: Introductionmentioning
confidence: 99%
“…12,18 Specific types of dementia, such as Huntington and Alzheimer diseases, are mentioned by case reports as potential predictors for suicidal behavior. 7,9,[18][19][20] Furthermore, early stages of dementia, 6,10,20 intact awareness of disease and its course, 6,[8][9][10]21 and accessibility to means 6,8 might increase the risk of suicide.Comorbid mental disorders, particularly mood disorders, are frequently listed as contributing to suicide in dementia patients. 6,9,10,19,22 Having dementia is found to increase the probability of developing depression, 23,24 Although depressive symptoms are found to predict cognitive decline, 25 there are diverging results on whether depression increases the probability of developing dementia.…”
mentioning
confidence: 99%